Impulses exerted in performing several kinds of swimming turns - Nicol, K.; Krueger, F. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The purpose of this study was to provide biomechanical descriptions and analyses of the flip turn and the open turn (orthodox freestyle turn) used in freestyle swimming.